Length Increase and Survival Rate of Coral Isopora palifera which Transplanted on Concrete Block - Roeroe, Wailan; Roeroe, Kakaskasen Andreas; Tilaar, Sandra O.; Manembu, Indri Shelovita; Mamangkey, Noldy G. F.; Schaduw, Joshian N. W. (Sam Ratulangi University, 2024)
Efforts to mitigate damage to coral reef ecosystems can be made by developing techniques for coral transplantation. The purpose is to know the survival rate of coral Isopora palifera and Measure the length increase of coral Isopora palifera using the Image-J application as the measurement. The research method was that artificial blocks made of concrete were used as containers for the installation of 27 colonies of coral Isopora palifera. Data collection in the field in the form of colonies that were successfully transplanted to artificial reef units will be explored using a camera from each concrete block which will take perpendicular pictures and colony portraits from each artificial reef unit. The results are then analyzed using the Image-J application. The transplantation results survival rate in Isopora palifera coral colonies in Paputungan village is 66.6% of 100%, while the Isopora palifera coral colony increase length was around 1.51 mm/5 months or 0.302 mm/month. Keywords: Coral, Isopora palifera, Transplant, Concrete block, North Sulawesi Abstrak Upaya penanggulangan kerusakan ekosistem terumbu karang dapat dilakukan dengan menggembangkan teknik transplantasi karang. Tujuan adalah Mengetahui tingkat ketahanan hidup karang Isopora palifera dan Mengetahui laju pertambahan karang Isopora palifera dengan menggunakan aplikasi Image-J sebagai pengukuran pertumbuhan. Metode penelitian yaitu balok buatan dari beton dijadikan wadah tempat pemasangan karang Isopora palifera sebanyak 27 koloni. Pengambilan data di lapangan berupa koloni yang berhasil ditransplantasi ke unit terumbu buatan akan didokumentasikan menggunakan kamera dari tiap-tiap balok diambil gambar tegak lurus dan memotret koloni dari masing-masing unit terumbu buatan. Hasil pemotretan tersebut selanjutnya dianalisa menggunakan aplikasi Image-J. Proses transplantasi di desa Paputungan menghasilkan 66,6% dari 100% tingkat kelangsungan hidup pada koloni karang Isopora palifera, sedangkan untuk laju pertabahan koloni karang Isopora palifera berada disekitar 1,51 mm/5 bulan atau 0,302 mm/bln. Kata Kunci: Karang, Isopora palifera, Transplantasi, Balok beton, Sulawesi Utara.